The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11145-018-9904-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating multiple source use among students with and without dyslexia

Abstract: Development of an instrument for measuring different types of cognitive load. Behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 173 publications
0
23
0
Order By: Relevance
“…However, Coiro (2011) found that even though prior topic knowledge played an important role in online research and comprehension performance of students with low online reading skills, it did not influence the performance of students with high online reading skills. Further, a recent study showed that even though prior topic knowledge was associated with knowledge acquisition after engaging with multiple web pages on a socio-scientific topic, it was not associated with multiple source integration (Andresen, Anmarkrud, & Bråten, 2018). These results suggest that prior knowledge is also an important factor in online research; however, further research is needed to better understand its role.…”
Section: The Relation Of Prior Knowledge Reasoning and Gender To LImentioning
confidence: 86%
See 1 more Smart Citation
“…However, Coiro (2011) found that even though prior topic knowledge played an important role in online research and comprehension performance of students with low online reading skills, it did not influence the performance of students with high online reading skills. Further, a recent study showed that even though prior topic knowledge was associated with knowledge acquisition after engaging with multiple web pages on a socio-scientific topic, it was not associated with multiple source integration (Andresen, Anmarkrud, & Bråten, 2018). These results suggest that prior knowledge is also an important factor in online research; however, further research is needed to better understand its role.…”
Section: The Relation Of Prior Knowledge Reasoning and Gender To LImentioning
confidence: 86%
“…Previous research has shown that good reading comprehension skills do not ensure students' success in integrating information from multiple texts (Stahl, Hynd, Britton, McNish, & Bosquet, 1996). Integrating information may also involve additional demands on working memory (Andresen et al, 2018;DeStefano & Levre, 2007). Additionally, students' attention and executive functions may contribute to their ORC performance, especially in synthesizing information.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This research is based on a sample of 22 tenth-graders with dyslexia who participated in a study investigating differences in multiple source use between students with and without dyslexia (Andresen, Anmarkrud, & Bråten, 2019). That study indicated that the group of students with dyslexia was heterogeneous with respect to working memory capacity and reading skill.…”
Section: The Present Studymentioning
confidence: 99%
“…The oral responses were audio-taped and transcribed before they were scored. Following Andresen et al (2019), the responses were scored in three steps. In the first step, we coded responses to both questions based on the extent to which participants integrated the two main perspectives represented in the materials (i.e., sun exposure is healthy vs. sun exposure is harmful), regardless of the web pages and representations they drew upon in their responses.…”
Section: Multiple Source Integration Taskmentioning
confidence: 99%
See 1 more Smart Citation